The Mechanics of Job Creation : Seizing the New Dividends of Globalization - Monga, Célestin (World Bank, Washington, DC, 2014)
This paper assesses some of the main strands of the theoretical literature on unemployment and employment and shows that their interesting conclusions may not be transferable to low-income countries whose endowment and production structures are profoundly different from that of high-income economies. It then tackles the knowledge deficit on employment creation by shedding light on the new economic opportunities that latecomers may derive from the dynamics of globalization -- especially the economic success of large emerging economies such as China and Brazil. It offers a simple analytical framework for identifying opportunities for labor arbitrage in the global economy and suggests a practical policy framework for exploiting them.